Is it time to personalise glucose targets during critical illness?. Issue 5 (5th September 2022) - Plummer, Mark P.; Hermanides, Jeroen; Deane, Adam M.
Abstract : Purpose of review: Dysglycaemia complicates most critical care admissions and is associated with harm, yet glucose targets, particularly in those with preexisting diabetes, remain controversial. This review will summarise advances in the literature regarding personalised glucose targets in the critically ill. Recent findings: Observational data suggest that the degree of chronic hyperglycaemia in critically ill patients with diabetes attenuates the relationship between mortality and several metrics of dysglycaemia, including blood glucose on admission, and mean blood glucose, glycaemic variability and hypoglycaemia in the intensive care unit. The interaction between acute and chronic hyperglycaemia has recently been quantified with novel metrics of relative glycaemia including the glycaemic gap and stress hyperglycaemia ratio. Small pilot studies provided preliminary data that higher blood glucose thresholds in critically ill patients with chronic hyperglycaemia may reduce complications of intravenous insulin therapy as assessed with biomakers. Although personalising glycaemic targets based on preexisting metabolic state is an appealing concept, the recently published CONTROLLING trial did not identify a mortality benefit with individualised glucose targets, and the effect of personalised glucose targets on patient-centred outcomes remains unknown. Summary: There is inadequate data to support adoption of personalised glucose targets into care of critically ill patients. However, there is a strong rationale empowering future trials utilising such an approach for patients with chronic hyperglycaemia.